Marketing-operations alignment: A review of the literature and theoretical background - Kedwadee Sombultawee; Sakun Boon-itt (Operations Research Perspectives, 2018)
The purpose of this paper is to consolidate existing knowledge and theories on marketing-operations alignment and theoretical background for this organizational alignment. The research used a qualitative literature review approach to identify key contributions to this area and incorporate them into theoretical background. Marketing-operations alignment, or organizational alignment between the marketing and operations functions of the firm, takes place at multiple levels (operational, tactical, and strategic). The literature reveals that the topic of operations alignment is a broad topic, spread across multiple journals and fields. Furthermore, there is no single dominant theory of alignment that can be applied. There is also substantial overlap with concepts of operational integration and coordination. The theoretical background uses configuration theory to model the fit of marketing and operations intelligence and decision-making at three points of interaction between these two functions.
Keywords: 330; OR in marketing; Alignment; Configuration theory; Marketing strategy; Operations strategy